In vitro binding of the asialoglycoprotein receptor to the beta adaptin of plasma membrane coated vesicles. - Beltzer, J P (1991)
The asialoglycoprotein (ASGP) receptor was used to probe total clathrin-coated vesicle proteins and purified adaptor proteins (APs) which had been fractionated by gel electrophoresis and transferred to nitrocellulose. The receptor was found to interact with proteins of approximately 100 kDa. The cytoplasmic domain of the ASGP receptor subunit H1 fused to dihydrofolate reductase competed for receptor binding to the 100 kDa polypeptide in the plasma membrane-type AP complexes (AP-2). A fusion protein containing the cytoplasmic domain of the endocytic mutant haemagglutinin HA-Y543 also competed, but a protein with the wild-type haemagglutinin sequence did not. This indicates that the observed interaction is specific for the cytoplasmic domain of the receptor and involves the tyrosine signal for endocytosis. When fractionated by gel electrophoresis in the presence of urea, the ASGP receptor binding polypeptide displayed a characteristic shift in electrophoretic mobility identifying it as the beta adaptin. Partial proteolysis of the AP-2 preparation followed by the receptor binding assay revealed that the aminoterminal domain of the beta adaptin contains the binding site for receptors.